2018
DOI: 10.1021/acs.inorgchem.8b02845
|View full text |Cite
|
Sign up to set email alerts
|

Emissive Azobenzenes Delivered on a Silver Coordination Polymer

Abstract: Azobenzene has become a ubiquitous component of functional molecules and polymeric materials because of the light-induced trans→cis isomerization of the diazene group. In contrast, there are very few applications utilizing azobenzene luminescence since excitation energy typically dissipates via non-radiative pathways. Inspired by our earlier studies with 2,2′-bis[N,N′-(2pyridyl)methyl]diaminoazobenzene (AzoAMoP) and related compounds, we investigated a series of five aminoazobenzene derivatives and their corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recent reports have suggested that gold nanoparticles can enhance the isomerization process in acyclic azobenzenes through gold‐mediated electron transfer, increasing the rate of the photoswitching (Figure ) . Azobenzene can also be functionalized and used as a ligand for coordination polymers (CP), including conducting the CPs . Recent reports have shown that silver‐based CPs exhibit electrical conductance, which begets the question of whether it is possible for such a polymer to exhibit differential electronic mobility upon switching with light (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have suggested that gold nanoparticles can enhance the isomerization process in acyclic azobenzenes through gold‐mediated electron transfer, increasing the rate of the photoswitching (Figure ) . Azobenzene can also be functionalized and used as a ligand for coordination polymers (CP), including conducting the CPs . Recent reports have shown that silver‐based CPs exhibit electrical conductance, which begets the question of whether it is possible for such a polymer to exhibit differential electronic mobility upon switching with light (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Azobenzene can also be functionalized and used as al igand for coordination polymers (CP), including conductingt he CPs. [45] Recent reportsh ave shown that silver-based CPs exhibit electrical conductance,w hich begetst he question of whether it is possible for such ap olymer to exhibit differential electronic mobility upon switching with light ( Figure 1). In this work we reportt he synthesis of ao ne-dimensional (1D) CP based on a cyclic-azobenzene coordinated to aA g + -ion.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating azobenzene ligands onto the side chains of struts can create photoresponsive MOFs. Azobenzene cis ← trans photoisomerization provides a technique to block MOF channels; however, azobenzene isomerization is nearly, or completely, restricted when the ligand is utilized as a structural support. Moreover, photochromic diarylethene derivatives have been incorporated as MOF struts, and local framework movement can be achieved by diarylethene ring opening and closing, but the framework change is minimal and the MOF skeleton is retained.…”
Section: Introductionmentioning
confidence: 99%
“…Azobenzene cis ! trans photoisomerization provides at echnique to block MOF channels; [5] however,a zobenzene isomerization is nearly, [6,7] or completely, [8,9] restrictedw hen the ligandi su tilized as as tructurals up-port. Moreover,p hotochromicd iarylethened erivatives have been incorporated as MOF struts,a nd local frameworkm ovement can be achieved by diarylethene ringo peninga nd closing, [10][11][12] but the framework change is minimal andt he MOF skeleton is retained.…”
Section: Introductionmentioning
confidence: 99%